2008
DOI: 10.1111/j.1467-9280.2008.02233.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month-Old Infants Benefit From Prior Experience in Statistical Learning

Abstract: A decade of research suggests that infants readily detect patterns in their environment, but it is unclear how such learning changes with experience. We tested how prior experience influences sensitivity to statistical regularities in an artificial language. Although 12-month-old infants learn adjacent relationships between word categories, they do not track nonadjacent relationships until 15 months. We asked whether 12-month-old infants could generalize experience with adjacent dependencies to nonadjacent one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
105
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 33 publications
8
105
1
Order By: Relevance
“…In the light of these findings, it is not surprising that the polarities of the pitch MMR and the rule MMR differ across sexes. The observed differences between boys and girls could be mediated by the hormone testosterone, which has been found to negatively impact phonological discrimination abilities in 1-mo-olds (32) and are in line with evidence showing that girls outperform boys in remote dependency learning at later developmental stages (i.e., at 12 mo) (18) and in general verbal abilities during childhood (26,34).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In the light of these findings, it is not surprising that the polarities of the pitch MMR and the rule MMR differ across sexes. The observed differences between boys and girls could be mediated by the hormone testosterone, which has been found to negatively impact phonological discrimination abilities in 1-mo-olds (32) and are in line with evidence showing that girls outperform boys in remote dependency learning at later developmental stages (i.e., at 12 mo) (18) and in general verbal abilities during childhood (26,34).…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies testing infants' learning of nonadjacent dependency rules behaviorally did not observe any learning before 12 mo of age (17,18). However, a recent ERP study indicated that infants might be sensitive to nonadjacent dependency rules in a novel language already at the age of 4 mo (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early on, infants need more concurrent exogenous cues such as high degree of similarity, same identity between the dependent pairs (Creel et al, 2004;Onnis et al, 2005) or prior exposure to them (Lany and Gómez, 2008;Lai and Poletiek, 2011) (for a review, see Perruchet et al, 2012), to help them to orient their attention to the relevant information (Pacton and Perruchet, 2008;Pacton et al, 2015), allowing a greater interaction between exogenous and endogenous attention. At later stages of development, after the first year of age, the improved endogenous system allows infants to rely less on the availability of these salient features to orient their attention to the relevant information.…”
Section: Learning More Challenging Non-adjacent Dependencies With Grementioning
confidence: 99%